2009
DOI: 10.1021/ja809516h
|View full text |Cite
|
Sign up to set email alerts
|

Melting Dramatically Enhances the Reactivity of Aluminum Nanoclusters

Abstract: The kinetic energy threshold for chemisorption of N(2) on Al(100)(+) has been measured as a function of the nanocluster's temperature from 440 to 790 K. When the Al(100)(+) cluster melts at 620-660 K, the threshold drops by approximately 1 eV (approximately 96 kJ/mol). A decrease in the activation energy of this magnitude causes a 10(8)-fold increase in the reaction rate at the melting temperature. The decrease in the activation energy may result from the mobility of the surface atoms on the liquid cluster, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 18 publications
3
63
0
Order By: Relevance
“…They have been studied in a series of experimental and the oretical works (see, for example, [4][5][6][7] and references Abstract-Segments of the potential energy surfaces corresponding to successive elementary stages of mul tistep fragmentation of nitrogen and diimine molecules upon their reaction with the aluminum cluster Al 13 and its doped analogue Al 12 Ti have been calculated by the density functional theory method. The minimum energy pathways of these reactions have been calculated for the stages of physisorption, chemisorption, and N 2 and N 2 H 2 fragmentation with different ways of insertion of fragments into the Al 13 and Al 12 Ti cages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have been studied in a series of experimental and the oretical works (see, for example, [4][5][6][7] and references Abstract-Segments of the potential energy surfaces corresponding to successive elementary stages of mul tistep fragmentation of nitrogen and diimine molecules upon their reaction with the aluminum cluster Al 13 and its doped analogue Al 12 Ti have been calculated by the density functional theory method. The minimum energy pathways of these reactions have been calculated for the stages of physisorption, chemisorption, and N 2 and N 2 H 2 fragmentation with different ways of insertion of fragments into the Al 13 and Al 12 Ti cages.…”
mentioning
confidence: 99%
“…They have been studied in a series of experimental and the oretical works (see, for example, [4][5][6][7] and references therein). A theoretical study of the reaction of N 2 with the perfect (111) surface of solid aluminum [4] has demonstrated that the reaction is highly exothermic and has a high activation barrier of ~3 eV.…”
mentioning
confidence: 99%
“…Calculations considering a liquid surface of aluminum show activation energies from 290 kJ mol À1 for a perpendicular orientation to the surface of the N 2 molecule up to 308.8 kJ mol À1 for a parallel orientation [46]. Cao et al [47] state that a melted aluminum surface might lower the activation energy of the dissociative adsorption of nitrogen. Our calculated energy barrier is 336.7 kJ mol À1 which is consistent with the previous results mentioned.…”
Section: Nitrogen (N 2 ) and Hydrogen (H 2 )mentioning
confidence: 99%
“…For example, the investigation by Jarrold et al revealed that the reactivity of Al clusters can be enhanced through cluster melting; 19 Mottet et al found the melting points of Ag clusters can be changed by doping; 20 The correlations with structural changes are often investigated to explore the melting behaviors of metal clusters in detail. For example, the distinct isomerization transitions occurred prior to its full melting for a 38-atom Co cluster; 21 Schebarchov et al found there is a structural change from the icosahedron to the decahedron in liquid-solid co-existing Ni cluster; 22 Wen et al specifically studied the shape transformation of a tetrahedral Pt cluster during its melting.…”
Section: Introductionmentioning
confidence: 99%